2015
DOI: 10.5507/bp.2014.015
|View full text |Cite
|
Sign up to set email alerts
|

Significance of serum mesothelin in an asbestos-exposed population in the Czech Republic

Abstract: Aims. Pleural mesothelioma is a highly aggressive and difficult-to-treat form of cancer induced by asbestos in 80-90% of cases. The population group most at risk of the condition are asbestos-exposed workers. Mesothelin or soluble mesothelin-related protein (SMRP) is studied as a potential marker of mesothelioma in the at-risk population. Methods. The study comprised 239 subjects with a mean duration of occupational exposure to asbestos of 19.9 years. In all of them, a complete medical history was taken, focus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 78 publications
1
9
0
1
Order By: Relevance
“…Furthermore, the relationship between SMRP values and asbestos exposure duration was examined in subjects occupationally exposed to asbestos. Our results support that there is no or weak correlation between SMRP levels and asbestos exposure duration [4,19,27]. So far, SMRP is not a desirable biomarker to discriminating the subjects exposed to asbestos from those without asbestos exposure, because the SMRP values were independent of the estimated exposure levels.…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…Furthermore, the relationship between SMRP values and asbestos exposure duration was examined in subjects occupationally exposed to asbestos. Our results support that there is no or weak correlation between SMRP levels and asbestos exposure duration [4,19,27]. So far, SMRP is not a desirable biomarker to discriminating the subjects exposed to asbestos from those without asbestos exposure, because the SMRP values were independent of the estimated exposure levels.…”
Section: Discussionsupporting
confidence: 74%
“…However, it was not feasible to discriminate healthy asbestos-exposed individuals from those with benign pleural and pulmonary disorders by using SMRP measurement. Previous studies indicated the possibility of SMRP to screen cases with pleural and lung disorders in asbestos-exposed population, although the efficiency of SMRP-based screening approach needs further investigation in prospective cohort studies [6,8,19,[26][27][28]. In these studies, few had evaluated the potential confounders influencing the value of SMRP [26][27][28].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the difference is not significant given the large confidence intervals (in particular for sensitivity, PPV, positive LR and DOR, as it has been already discussed), mainly due to the low number of MM cases in the present study. Numerous other studies have confirmed the diagnostic yield and convenience of the use of SMRP concentrations for the diagnosis of MM, often recommending consideration of further diagnostic steps in case of positive results [5,13,[27][28][29][30]. For instance, in a recent review, Cristaudo et al have stated that SMRP levels seem to be the most adequate biomarker for MM in spite of the fact that they may be genetically and clinically affected [2].…”
Section: Ijomeh 2016;29(3)mentioning
confidence: 99%
“…A recent review reported a meta analysis of 30 publications to determine the sensitivity and specificity of SMRP as a biomarker of mesothelioma [90]. Studies on occupational exposure to asbestos in the Czech Republic revealed distinguishing serum levels of SMRP in which exposed subjects with benign disease had higher levels than normal subjects but lower levels than subjects with MM as determined by CXRs [91]. An additional study from Australia used a sandwich ELISA with two monoclonal antibodies (OV569 and 4H3) comparing a non-exposed control group of 28 controls with 40 asbestos exposed (Table 1) [55].…”
Section: Protein Biomarkersmentioning
confidence: 99%